A comprehensive and universal approach for embryo testing in patients with different genetic disorders. Issue 7 (8th July 2021) - Zhang, Shuo; Lei, Caixia; Wu, Junping; Xiao, Min; Zhou, Jing; Zhu, Saijuan; Fu, Jing; Lu, Daru; Sun, Xiaoxi; Xu, Congjian
Abstract: Background: In vitro fertilization (IVF) with preimplantation genetic testing (PGT) has markedly improved clinical pregnancy outcomes for carriers of gene mutations or chromosomal structural rearrangements by the selection of embryos free of disease‐causing genes and chromosome abnormalities. However, for detecting whole or segmental chromosome aneuploidies, gene variants or balanced chromosome rearrangements in the same embryo require separate procedures, and none of the existing detection platforms is universal for all patients with different genetic disorders. Methods: Here, we report a cost‐effective, family‐based haplotype phasing approach that can simultaneously evaluate multiple genetic variants, including monogenic disorders, aneuploidy, and balanced chromosome rearrangements in the same embryo with a single test. A total of 12 monogenic diseases carrier couples and either of them carried chromosomal rearrangements were enrolled simultaneously in this present study. Genome‐wide genotyping was performed with single‐nucleotide polymorphism (SNP)‐array, and aneuploidies were analyzed through SNP allele frequency and Log R ratio. Parental haplotypes were phased by an available genotype from a close relative, and the embryonic genome‐wide haplotypes were determined through family haplotype linkage analysis (FHLA). Disease‐causing genes and chromosomal rearrangements were detected by haplotypes located within the 2 Mb region covering the targeted genes or breakpoint regions. Results: Twelve blastocysts were thawed, and then transferred into the uterus of female patients. Nine pregnancies had reached the second trimester and five healthy babies have been born. Fetus validation results, performed with the amniotic fluid or umbilical cord blood samples, were consistent with those at the blastocyst stage diagnosed by PGT. Conclusions: We demonstrate that SNP‐based FHLA enables the accurate genetic detection of a wide spectrum of monogenic diseases and chromosome abnormalities in embryos, preventing the transfer of parental genetic abnormalities to the fetus. This method can be implemented as a universal platform for embryo testing in patients with different genetic disorders. Abstract : 1. We report a cost‐effective, comprehensive, and universal platform for embryo testing in patients with different genetic disorders. 2. SNP‐based FHLA enables the accurate genetic detection for a wide spectrum of monogenic diseases and chromosome rearrangements in embryos. 3. This proposed strategy may markedly improve the precision of embryo testing and prevent the birth of affected fetuses.